OSMR gene effect on the pathogenesis of chronic autoimmune Urticaria via the JAK/STAT3 pathway - Xiao-Yan Luo; Qun Liu; Huan Yang; Qi Tan; Li-Qiang Gan; Fa-Liang Ren; Hua Wang (BMC, 2018)
Abstract Background Chronic autoimmune urticaria (CAU) is a common skin disease and remains unclear understanding of pathogenesis in the vast majority of cases. In order to explore a new therapy for CAU, the current study was performed to investigate the possible functioning of the Oncostatin M receptor (OSMR) gene in the autoimmunity of CAU via regulation of the JAK/STAT3 signaling pathway. Methods CAU skin tissues from 24 CAU patients and normal skin tissues from normal subjects were collected. Hematoxylin-eosin (HE) staining was conducted to count eosinophils, and immunohistochemistry was carried out to detect the positive rate of OSMR expression in two kinds of skin tissues. A total of 72 Kunming (KM) mice were selected, and 60 mice were used for establishing CAU models and later transfected with different plasmids. The expression of inflammatory factors was evaluated by enzyme-linked immunosorbent assays (ELISA). Expressions of janus kinase (JAK), signal transducer and activator of transcription 3 (STAT3), interferon-stimulated gene 15 (ISG15), CT10-regulated kinase (CRK), and interferon regulatory factor 9 (IRF9) were identified using Western blot assay and reverse transcription quantitative polymerase chain reaction (RT-qPCR). Epithelial cell proliferation was assessed by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT) assay, and cell cycle distribution and cell apoptosis were assessed using flow cytometry. Results The findings confirm that OSMR protein expression and histamine release rate are highly elevated in human CAU skin tissues, and the expression of the JAK/STAT3 signaling pathway-related genes (OSMR, JAK2, STAT3, ISG15, CRK and IRF9) was up-regulated. OSMR gene silencing in CAU mice significantly decreases the content of inflammatory factors (IL-1, IL-6, IFN-γ, and IgE), the number of eosinophils, and reduces the expression of the JAK/STAT3 signaling pathway related genes, and further enhances cell proliferation, promotes cell cycle entry and inhibits apoptosis of epithelial cells. Conclusion All aforementioned results indicate that OSMR gene silencing inhibits the activation of the JAK/STAT3 signaling pathway, thereby suppressing the development of CAU.